2015
DOI: 10.1111/aor.12637
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes With HeartWare HVAD as Bridge to Transplant in Children: A Single Institution Experience

Abstract: The HeartWare HVAD has been used as a bridge to cardiac transplantation in the pediatric population. We describe outcomes following HeartWare HVAD implantation at a single center. A retrospective chart review was performed of all HeartWare HVAD implants performed at our institution between May 2013 and March 2015. Eight children between the ages of 9 and 17 years underwent HVAD implantation as a bridge to transplant (N = 7 cardiomyopathy, N = 1 complex single ventricle). There was one operative death in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Current options for VAD use in children include pulsatile paracorporeal devices, continuous flow paracorporeal devices, and implantable continuous flow devices, but applicability varies, depending on patient age, size, and diagnosis (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Due to the improved outcomes reported with implantable, continuous flow VADs in adults, many pediatric centers have more recently adopted this strategy for adolescent end-stage heart failure, often implanting the HeartWare ventricular assist device (HVAD, Framingham, MA, USA) in these patients (2)(3)(4)13,14). While pediatric HVAD application has indeed increased since the first reported use in 2012 as a bridge to heart transplantation in an adolescent (15), determining candidacy and timing for initiation of pediatric VAD support has remained a challenge.…”
mentioning
confidence: 99%
“…Current options for VAD use in children include pulsatile paracorporeal devices, continuous flow paracorporeal devices, and implantable continuous flow devices, but applicability varies, depending on patient age, size, and diagnosis (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Due to the improved outcomes reported with implantable, continuous flow VADs in adults, many pediatric centers have more recently adopted this strategy for adolescent end-stage heart failure, often implanting the HeartWare ventricular assist device (HVAD, Framingham, MA, USA) in these patients (2)(3)(4)13,14). While pediatric HVAD application has indeed increased since the first reported use in 2012 as a bridge to heart transplantation in an adolescent (15), determining candidacy and timing for initiation of pediatric VAD support has remained a challenge.…”
mentioning
confidence: 99%
“…Irving et al reported on a series of patients in whom a structured protocol was used to assess readiness for EXCOR explantation. 45 Patients were formally tested after 2-4 weeks of support to find out whether there was evidence of at least near-normalisation of systolic function. Testing included echocardiographic, invasive pressure, and blood gas monitoring with and without pharmacological stress over a 90-to 120-minute period; 11 explants occurred in 10 patients.…”
Section: Outcomes Of Ventricular Assist Device Use In Childrenmentioning
confidence: 99%
“…Although much of the early study of mechanical circulatory support in children has focussed on establishing the benefit of these devices to reduce wait-list mortality and achieve successful transplant, there are emerging reports on myocardial recovery. Irving et al reported on a series of patients in whom a structured protocol was used to assess readiness for EXCOR explantation 45 . Patients were formally tested after 2–4 weeks of support to find out whether there was evidence of at least near-normalisation of systolic function.…”
Section: Mechanical Circulatory Supportmentioning
confidence: 99%
“…Several devices for long‐term support are readily available in the USA and Europe for adults, but fewer options are available for children . The Berlin Heart EXCOR Pediatric ventricular assist device (VAD) represents the most important tool for long‐term support to help pediatric patients of all age groups, from newborns to teenagers, to survive until a donor heart can be identified.…”
Section: Introductionmentioning
confidence: 99%